2005
DOI: 10.1111/j.1532-849x.2005.00020.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a New Denture Adhesive on Bite Force Until Denture Dislodgement

Abstract: The results of this in vivo study suggest that the denture adhesive tested could effectively increase BFDD for up to 6 hours after application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
0
10

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 14 publications
4
46
0
10
Order By: Relevance
“…6,7 It has been shown that the use of denture adhesives significantly increase retention and stability of dentures and biting force, providing patients with a greater feeling of satis-faction. [7][8][9][10][11][12][13][14][15][16] Furthermore, denture adhesives are effective in providing psychological comfort to patients. Kapur 8 reported that the use of denture adhesives did not significantly improve masticatory performance with the sieving method using peanuts.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 It has been shown that the use of denture adhesives significantly increase retention and stability of dentures and biting force, providing patients with a greater feeling of satis-faction. [7][8][9][10][11][12][13][14][15][16] Furthermore, denture adhesives are effective in providing psychological comfort to patients. Kapur 8 reported that the use of denture adhesives did not significantly improve masticatory performance with the sieving method using peanuts.…”
Section: Introductionmentioning
confidence: 99%
“…An ideal denture adhesive should retain its adhesive properties for 12 to 16 h before requiring re-application 12) , and the initial viscosity should allow easy manipulation without compromising the adhesive strength. Koronis et al 11) and Uysal et al 15) found that only 68-75.7% of people surveyed reported that the retentive capacity of denture adhesives lasted for more than 2 h. However, several other studies reported that denture adhesives can remain effective for more than 8 h 16,17) , with the retentive capacity peaking at 2 to 4 h after application 16,17) , Influence of composition on the adhesive strength and initial viscosity of denture adhesives Jian- 16,17) . In our preliminary study, a lot of commercial denture adhesives were the tendencies that the adhesive strength decreased after immersed into water for 1-2 h. However, in the clinical situation, it is necessary that the maximum adhesive strength can be lasted for more than 6 h. The small period of effective retention offered by denture adhesives may be the reason why some denture wearers apply them several times a day in order to keep their dentures in place.…”
Section: Introductionmentioning
confidence: 99%
“…When a denture adhesive is immersed in water, the water-soluble polymers are degraded, thereby increasing its viscosity and adhesive strength. 7,21,22 However, the samples containing herbal medicine components consisted of base material (the control group) with herbal medicine. When the adhesive strength was measured using the same amounts of material, the total amount of water-soluble polymer was, apparently, smaller than that in the control samples, resulting in a small water solubility-associated increase in the viscosity.…”
Section: Discussionmentioning
confidence: 99%
“…8 When patients use glue type denture adhesives (classified into cream-form, powder-form and sheet-form denture adhesives) under a dentist's supervision, these prove effective in improving denture stability and retention. [4][5][6][7] The primary components of cream-form denture adhesives are water-soluble polymers and white petrolatum. In the oral cavity, the water-soluble polymers absorb saliva, thereby increasing viscosity and adhesion strength.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation